Protective Signature of IFNγ-Stimulated Microglia Relies on miR-124-3p Regulation From the Secretome Released by Mutant APP Swedish Neuronal Cells - Garcia, Gonçalo; Fernandes, Adelaide; Stein, Frank; Brites, Dora (Frontiers in Pharmacology, 2022)
Microglia-associated inflammation and miRNA dysregulation are key players in Alzheimer’s disease (AD) pathophysiology. Previously, we showed miR-124 upregulation in APP Swedish SH-SY5Y (SWE) and PSEN1 iPSC-derived neurons, and its propagation by the secretome (soluble and exosomal fractions). After modulation with miR-124 mimic/inhibitor, we identified common responsive mechanisms between such models. We also reported miR-124 colocalization with microglia in AD patient hippocampi. Here, we determined how miR-124 modulation in SWE cells influences microglia polarized subtypes, in the context of inflammation. For that, we separately cultured miR-124 modulated SWE cells with the human CHME3 microglia stimulated with interferon gamma (IFNγ-MG) and assessed their adopted gene/miRNA profile and proteomic signature. The presence of miR-124 in SWE cells/secretome (soluble and exosomal), led to its upregulation in IFNγ-MG microglia. Treatment of SWE cells with miR-124 inhibition led to RAGE overexpression and loss of neuronal viability, while the mimic caused RAGE/HMGB1 downregulation and prevented mitochondria membrane potential loss. When accessing the paracrine effects on microglia, SWE miR-124 inhibition favored their IFNγ-induced inflammatory signature (upregulated RAGE/HMGB1/iNOS/IL-1β; downregulated IL-10/ARG-1), while the mimic reduced microglia activation (downregulated TNF-α/iNOS) and deactivated extracellular MMP-2/MMP-9 levels. Microglia proteomics identified 113 proteins as being responsive to SWE miR-124 levels, including a subgroup of 17 proteins involved in immune function/inflammation and/or miR-124 targets. A total of 72 proteins were upregulated (e.g., PAWR and EFEMP1) and 21 down-regulated (e.g., MAP2K6) by the mimic, while the inhibitor also up-regulated 21 proteins and down-regulated 17 (e.g., TGFB1, PAWR and EFEMP1). Other targets were associated with neurodevelopmental mechanisms, synaptic function, and vesicular trafficking. To examine the source of miR-124 variations in microglia, we silenced the RNase III endonuclease Dicer1 to block miRNA canonical biogenesis. Despite this suppression, the coculture with SWE cells/exosomes still raised microglial miR-124 levels, evidencing miR-124 transfer from neurons to microglia. This study is pioneer in elucidating that neuronal miR-124 reshapes microglia plasticity and in revealing the relevance of neuronal survival in mechanisms underlying inflammation in AD-associated neurodegeneration. These novel insights pave the way for the application of miRNA-based neuropharmacological strategies in AD, whenever dysregulated levels are identified during patient stratification.